Influence of Bushen Tiaochong Cycle Therapy on Th1/Th2 Deviation, Sex Hormone Level, and Pregnancy Outcome of Alloimmune Recurrent Spontaneous Abortion. (21st September 2021) - Wang, Peng; Jiang, Guilin; Ju, Wenjuan; Cai, Yaping; Wang, Jinrong; Wu, Feihua
Abstract : Objective . To analyze the influence of Bushen Tiaochong cycle therapy on Th1/Th2 deviation, sex hormone level, and pregnancy outcome of alloimmune recurrent spontaneous abortion (RSA). Methods . From August 2018 to April 2020, 130 patients with alloimmune RSA who met the inclusion criteria were randomly divided into the control group ( n = 65) and the study group ( n = 65). The former received lymphocyte immunotherapy (LIT), and the latter received Bushen Tiaochong cycle therapy on the basis of LIT. The treatment ended at 12 w of pregnancy. The total score of traditional Chinese medicine (TCM) syndromes, Th1 cytokine (IL-2), Th2 cytokine (IL-10), and related hormones (chorionic gonadotropin (hCG) and progesterone (P)) were compared between the two groups before and after treatment. The positive rate of blocking antibody (BA), pregnancy success rate, and preterm birth rate were counted. Result . After treatment, the total score of TCM syndromes, IL-2 level, and Th1/Th2 ratio in the two groups decreased significantly, while the levels of IL-10, hCG, and P increased significantly, and the study group improved significantly compared with the control group (P < 0.05 ). The positive rate of BA and pregnancy success rate in the study group were higher than those in the control group (P < 0.05 ). There was no significant difference in the preterm birth rate between the two groups (P > 0.05 ). Conclusion . On the basis of routine western medicine treatment, a combined application of Bushen Tiaochong cycle therapy can significantly improve the Th1/Th2 deviation, serum sex hormone level, and pregnancy outcome in patients with alloimmune RSA.